Searching for a Room of One’s Own: Rethinking the Iranian Diaspora in “Persepolis”, “Shahs of Sunset” and “A Girl Walks Home Alone at Night” - Emily Edwards (Glocalism: Journal of Culture, Politics and Innovation)
For diasporic communities created through violence or forcible resettlement, home transcends physical boundaries and becomes a blend of past experience and future imagination. Iranians displaced after the 1979 Revolution have imagined home through various cultural mediums, such as, television, film, and literature. Three cultural texts produced by Iranian women, (Persepolis, Shahs of Sunset, and A Girl Walks Home Alone at Night), in particular, offer illuminating glimpses into the diaspora experience. I propose to engage in a close textual reading of the aforementioned works across methodological boundaries to show that despite their portrayal of varied diaspora life experiences, the diaspora paradigm reduces these experiences to a figurative return to the homeland. I argue that the diaspora paradigm, by offering a highly romanticized and homogenizing understanding of home and foreign land, flattens the diversity of identity and experience. Furthermore, the diaspora paradigm denies the role of intersection of class and gender on the lived experiences of the actual diaspora population. Through an alternative reading of these texts, I hope to challenge the prevalent paradigm through which Iranian diaspora identity is understood. I focus on autobiographical textual trends as a method of story-telling and self-formation, comparing this narrative structure to the theory of identity as ‘infinitely postponed’ in exile. I specifically highlight crucial interactions of local and global forces that shape diaspora experiences otherwise elided in the existing scholarship, complicating romantic understandings of both home and abroad.